Correction: Impact of non-invasive oxygen reserve index versus standard SpO2 monitoring on peripheral oxygen saturation during endotracheal intubation in the intensive care unit: Protocol for the randomized controlled trial NESOI2. - Hugo Hille; Aurélie Le Thuaut; Pierre Asfar; Quentin Quelven; Emmanuelle Mercier; Anthony Le Meur; Jean-Pierre Quenot; Virginie Lemiale; Grégoire Muller; Martin Cour; Alexis Ferré; Asael Berger; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0307723.].